A Novel Deletion Mutation of Exon 2 of the C19orf12 Gene in an Omani Family with Mitochondrial Membrane Protein-Associated Neurodegeneration (MPAN) - Nabil Al Macki; Ismail Al Rashdi (Oman Medical Journal, 2017)
Mutations in the C19orf12 gene are known to cause mitochondrial membrane protein-associated neurodegeneration (MPAN), which is a neurodegeneration with brain iron accumulation (NBIA) type 4 disorder. To the best of our knowledge, this is the first report of a genetically confirmed case of MPAN from Oman. A novel homozygous deletion of exon 2 of the C19orf12 gene was confirmed on the proband, a seven-year-old girl, who presented with gait instability. Brain magnetic resonance imaging showed iron deposition on the basal ganglia. This report highlights the importance of genetic testing of such a clinically and genetically heterogeneous condition among a population with a high consanguinity rate. To overcome the diagnostic difficulty, implementation of a cost-effective approach to perform cascade screening of carriers at risk is needed as well as programs to address risky consanguineous marriages.